2016
DOI: 10.1021/acsnano.6b06200
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linked Fluorescent Supramolecular Nanoparticles as Finite Tattoo Pigments with Controllable Intradermal Retention Times

Abstract: Tattooing has been utilized by the medical community for precisely demarcating anatomic landmarks. This practice is especially important for identifying biopsy sites of nonmelanoma skin cancer (NMSC) due to the long interval (i.e., up to 3 months) between the initial diagnostic biopsy and surgical treatment. Commercially available tattoo pigments possess several issues, which include causing poor cosmesis, being mistaken for a melanocytic lesion, requiring additional removal procedures when no longer desired, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 46 publications
(87 reference statements)
1
20
0
Order By: Relevance
“…The multivalent Ad/CD molecular recognition allows modular control over the sizes, surface chemistry, and payloads of SMNP vectors, promising a diversity of imaging [ 18,19 ] and therapeutic applications. [ 20 ] We have shown that this self‐assembly strategy can be utilized for combinatorial formulation and screening of SMNPs to optimize formulations with significantly improved delivery performance. [ 21 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The multivalent Ad/CD molecular recognition allows modular control over the sizes, surface chemistry, and payloads of SMNP vectors, promising a diversity of imaging [ 18,19 ] and therapeutic applications. [ 20 ] We have shown that this self‐assembly strategy can be utilized for combinatorial formulation and screening of SMNPs to optimize formulations with significantly improved delivery performance. [ 21 ]…”
Section: Methodsmentioning
confidence: 99%
“…Our self‐assembly strategy [ 18 ] enables precise control over two synthetic variables—(i) Ad‐PAMAM/CD‐PEI ratios, and (ii) the coverage of a membrane penetration ligand, TAT. [ 20c ] Through small‐scale combinatorial screenings, optimal performances were identified for the formulations of Cas9/sgRNA‐plasmid⊂SMNPs and Donor‐RS1/GFP‐plasmid⊂SMNPs according to their performances for inducing CRISPR/Cas9‐mediated insertion and deletion events (indels) and GFP transfection, respectively. The two optimized SMNP vectors were then employed to achieve CRISPR/Cas9‐mediated knockin of RS1/GFP gene in growth‐synchronized B16 cells.…”
Section: Methodsmentioning
confidence: 99%
“…Tseng and co‐workers constructed a micrometer‐sized fluorescent supramolecular material as finite tattoo pigments, encapsulating a fluorescent conjugated polymer using the supramolecular approach and displaying the size‐dependent intradermal time. [ 104 ] Typically, Liu and co‐workers developed novel fluorescent supramolecular nanoparticles, consisting of β‐CD‐modified hyaluronic acid and TPE‐modified adamantane. [ 105 ] This supramolecular assembly exhibited enhanced fluorescent emission owing to the TPE cores condensed by host–guest interaction, which could be used for targeted‐imaging of cancer cells.…”
Section: Supramolecular Macrocycle‐guided Assembly Via Host–guest Intmentioning
confidence: 99%
“…Previously, we reported a flexible self‐assembled approach for preparing supramolecular nanoparticle (SMNP) vectors [ 22 ] via mixing three common molecular building blocks, that is, adamantane‐grafted polyamidoamine dendrimer (Ad‐PAMAM), adamantane‐grafted poly(ethylene glycol) (Ad‐PEG), and β‐cyclodextrin‐grafted polyethyleneimine (CD‐PEI). By leveraging multivalent molecular interactions between β‐cyclodextrin (CD) and adamantane (Ad) motifs, modular control over the surface chemistry, sizes, and payloads of the nanoparticles can be easily achieved, offering a versatile playground for various diagnostic imaging [ 23 ] and therapeutic applications. [ 24 ] Inspired by existing substrate‐mediated delivery approaches, [ 25 ] we developed a supramolecular nanosubstrate‐mediated delivery (SNMD) strategy [ 26 ] to improve the delivery efficiency of SMNP vectors, where Ad‐grafted silicon nanowire substrates (Ad‐SiNWS) were designed for dynamic assembly and local enrichment of SMNPs.…”
Section: Introductionmentioning
confidence: 99%
“…By leveraging multivalent molecular interactions between β‐cyclodextrin (CD) and adamantane (Ad) motifs, modular control over the surface chemistry, sizes, and payloads of the nanoparticles can be easily achieved, offering a versatile playground for various diagnostic imaging [ 23 ] and therapeutic applications. [ 24 ] Inspired by existing substrate‐mediated delivery approaches, [ 25 ] we developed a supramolecular nanosubstrate‐mediated delivery (SNMD) strategy [ 26 ] to improve the delivery efficiency of SMNP vectors, where Ad‐grafted silicon nanowire substrates (Ad‐SiNWS) were designed for dynamic assembly and local enrichment of SMNPs. As cells settle onto the substrates, their membranes form intimate contacts with the nanowires and generate transient defects that facilitate intracellular uptake of SMNPs.…”
Section: Introductionmentioning
confidence: 99%